2015
DOI: 10.1016/j.bbamem.2014.11.029
|View full text |Cite
|
Sign up to set email alerts
|

TRH-receptor mobility and function in intact and cholesterol-depleted plasma membrane of HEK293 cells stably expressing TRH-R-eGFP

Abstract: the presence of an unaltered level of cholesterol in the plasma membrane represents an obligatory condition for an optimum functioning of TRH-R signaling cascade. The decreased order and increased fluidity of hydrophobic membrane interior suggest an important role of this membrane area in TRH-R-Gq/G11α protein coupling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 84 publications
3
14
0
1
Order By: Relevance
“…Removal of cholesterol by β-MCD reduced lateral mobility of FP receptors and increased residence time. These data are in agreement with previous studies where acute depletion of cholesterol reduces mobility of membrane proteins and increases confinement [53,54]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Removal of cholesterol by β-MCD reduced lateral mobility of FP receptors and increased residence time. These data are in agreement with previous studies where acute depletion of cholesterol reduces mobility of membrane proteins and increases confinement [53,54]. …”
Section: Discussionsupporting
confidence: 93%
“…The concentration of β-MCD used in this study removes approximately 80% of the cholesterol [55] which would allow for packing of acyl chains reducing fluidity of the membrane and most likely lateral mobility of the FP receptor. Acute depletion of cholesterol in the present study also increased residence time of FP receptors which has been shown in previous studies in which acute or chronic depletion of cholesterol increased confinement of membrane-bound proteins [53,54]. Depletion of membrane cholesterol results in reorganization of the cytoskeleton and phosphatidylinositol which may lead to increased confinement of membrane-bound receptors.…”
Section: Discussionsupporting
confidence: 86%
“…We obtained values for CD95 diffusion coefficient that were comparable with values found in the literature for other membrane receptors [62][63][64][65][66]. The values for the diffusion coefficient of CD95 obtained by FCS and FRAP were within the same order of magnitude and the results obtained with both techniques showed the same tendency; namely a decrease in CD95 diffusion when the cells were in contact with the agonistic antibody.…”
Section: Discussionsupporting
confidence: 87%
“…RICS has been applied to analyze membrane proteins [ 25 , 26 ], DNA [ 27 ], and other biomolecules [ 28 , 29 ] because it provides the spatial distribution of the diffusional coefficients in the diffusion map [ 27 , 30 ]. Each brick constituting the diffusion map showed the diffusion property of biomolecules contained in each microdomain.…”
Section: Introductionmentioning
confidence: 99%